The Efforts Of Islamic Religious Education Teachers In Improving The Learning Outcomes Of Fifth-Grade Students At Alam Pelopor Elementary School On Hajj Material Using The Tgt (Team Games Tournament) Cooperative Learning Method - Rahmat Chaerudin; Delis Sri Maryati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Many fifth-grade students have not yet achieved the expected competency standards in understanding Hajj material, so it is important to take action to improve student understanding. This study used TKP, more specifically the TGT (Team Games Tournament) type, with a sample of 26 students, consisting of 14 boys and 12 girls. In the first test, quite a few students did not achieve the standard score. However, after implementing the TGT method in Cycle I and Cycle II, there was significant progress among the fifth-grade students at SD Alam Pelopor, indicating that the TGT method is effective for use in teaching students.